Developing Cultural Competence through Problem Posing and Multicultural Children's Literature - Gayla Lohfink; Laurie Curtis (The Advocate, 2012)
Increasing diversity in Kansas elementary schools is challenging educators to teach culturally and linguistically diverse students effectively. Unfortunately, research shows teachers as lacking in necessary cultural competencies. This article shares a multicultural picture book action-research project and shows how pre-service teachers constructed pedagogy by selecting literature that drew upon their students’ funds of knowledge. Implementation of the same project in practicing teachers’ classrooms revealed their self-reflections of students’ cultural connections frequently, but more often, the teachers’ reflections focused on students’ connections to the curriculum. This observation prompted an alternative problem-posing approach for utilizing multicultural literature to be presented for teachers. Implementing multicultural children’s literature…has helped me to see that my students grow up different than I did and come from different backgrounds and have different families than I do, and it is something I need to remember when planning for my students… [and] not try to get students to fit into the way I feel comfortable teaching… (Pre-service teacher’s self-reflection after reading aloud a multicultural picture book in a practicum setting - March, 2012). Transforming one’s cultural landscape, as this pre-service teacher’s reflection demonstrates, requires examining one’s personal understandings and recognizing “vacancies” in previous experiences—holes that when recognized leave lasting impressions and prompt one to change the “status quo in education” (Szecsi, Spillman, Vázquez-Montilla, & Mayberry, 2010, p. 44). Teacher education programs have worked at bringing about changes in mainstream education and particularly the cultural competencies of their candidates for some time (Ming & Dukes, 2006). Incorporating multicultural educational training to facilitate candidates’ awareness, knowledge, and skills to more successfully teach students from cultures other than their own is common (Pang, Stein, Gomez, matas, & Shimogori, 2011). Unfortunately, research shows that while practicing teachers are aware and knowledgeable of diversity issues and support multicultural teaching, they fail to consistently and effectively implement cultural practices in their classrooms (Leighton & Harkins, 2010). Such evidence, coupled with the growing diversity in our Kansas elementary classrooms (Center for Public Education, 2009), urges us, as literacy teacher educators, to seek ways that better develop our preservice and (ultimately) practicing teachers’ cultural competencies. As such, the intent of this article is to share our multicultural picture book action-resarch project (Author & Author, 2012) and show how pre-service teachers construct pedagogy by selecting literature that draws upon their students’ “funds of knowledge” (Moll, Amanti, Neff, & Gonzalez, 1992, p. 133). We also examine how such pedagogy alone does not result in culturally competent teachers with “behaviors that illustrate culturally sensitive interactions with diverse groups” (Leighton & Harkins, 2010) and offer an approach for how elementary teachers might utilize multicultural literature to further deepen their cultural teaching competencies.